2015
DOI: 10.1007/s00726-015-2128-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthesis capacity, ambulatory blood pressure and end organ damage in a black and white population: the SABPA study

Abstract: Nitric oxide (NO) synthesis capacity is determined by the availability of substrate(s) such as L-arginine and the influence of nitric oxide synthase (NOS) inhibitors, asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA). These factors may be important in black South Africans with a very high prevalence of hypertension. We compared ambulatory blood pressure (BP), markers of end organ damage and NO synthesis capacity markers [L-arginine, L-homoarginine, L-citrulline, L-arginine:ADMA, ADMA, SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…Higher baseline levels of specific metabolites were associated with older age, hypertension, and higher BMI, which is consistent with previous studies showing these metabolites as general markers of cardiovascular disease risk (18,20,27). African Americans had lower baseline levels of ADMA and SDMA, which is consistent with previously described ethnic distributions that had demonstrated higher redox status in this population (2830). However, African Americans also had a slightly greater degree of cardiovascular comorbidities—including more hypertension (52% vs. 20%), diabetes (16% vs. 4%), and larger BMI (median 31 vs. 25)—at baseline as compared to Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…Higher baseline levels of specific metabolites were associated with older age, hypertension, and higher BMI, which is consistent with previous studies showing these metabolites as general markers of cardiovascular disease risk (18,20,27). African Americans had lower baseline levels of ADMA and SDMA, which is consistent with previously described ethnic distributions that had demonstrated higher redox status in this population (2830). However, African Americans also had a slightly greater degree of cardiovascular comorbidities—including more hypertension (52% vs. 20%), diabetes (16% vs. 4%), and larger BMI (median 31 vs. 25)—at baseline as compared to Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…None of the PADiMe indices were found to be associated with BP in the ASOS and African-PREDICT studies, which included healthy participants. The findings of the present study support the observations of the lower circulating ADMA and SDMA concentrations in black subjects measured in the SABPA study [44]. Low urinary excretion of ADMA is a cardiovascular risk factor in white adults [45,46].…”
Section: Arg Dimethylation and Blood Pressuresupporting
confidence: 90%
“…In previous bi-ethnic studies, serum ADMA and SDMA concentrations were found not to differ between black and white men [43]. In the SABPA (Sympathetic Activity and Ambulatory Blood Pressure in Africans) study, black men and women had higher BP and albumin-to-creatinine ratios, higher plasma concentrations of the NOS substrate Arg, and even lower plasma concentrations of ADMA and SDMA, the NOS inhibitors, compared to white men [28,44].…”
Section: Arg Dimethylation and Blood Pressurementioning
confidence: 73%
“…Unique genetic polymorphisms of MYH9 and apolipoprotein L1 genes are associated with the development of kidney disease in blacks [26,27]. Detailed studies of the Genetic Risk Assessment of Heart Failure in African-Americans registries are currently shedding light on the genetic frequency of aldosterone synthase (CYP11B2) and endothelial constitutive nitric oxide synthase within both black and white populations [17,[31][32][33]. More specifically, a common polymorphism identified within the CYP11B2 gene has been linked to HTN by promoting higher than normal levels of aldosterone synthase activity.…”
Section: Genetic Mechanisms In Hypertensionmentioning
confidence: 99%